Flavonoids against depression: a comprehensive review of literature - Alaleh Alizadeh; Yeganeh Pourfallah-Taft; Maryam Khoshnazar; Aysan Safdari; Saba Vafadar Komari; Mehrnaz Zanganeh; Nafiseh Sami; Maryam Valizadeh; Arezoo Faridzadeh; Arezoo Faridzadeh; Dorsa Alijanzadeh; Seyed Amirhossein Mazhari; et al. (Frontiers Media S.A., 2024)
BackgroundDepression is a state of low mood and aversion to activity, which affects a person's thoughts, behavior, motivation, feelings, and sense of wellbeing. Pharmacologic therapies are still the best effective treatment of depression. Still, most antidepressant drugs have low efficacy and delayed onset of therapeutic action, have different side effects, and even exacerbate depression. Such conditions make it possible to look for alternatives. Consequently, we decided to summarize the impact of flavonoids on depression in this review.MethodsWe searched scientific databases such as SCOPUS, PubMed, and Google Scholar to find relevant studies until July 2022.ResultsA wide variety of natural components have been shown to alleviate depression, one of which is flavonoids. Due to the growing tendency to use natural antidepressant drugs, scientific studies are increasingly being conducted on flavonoids. This study aims to review the latest scientific researches that indicate the antidepressant potential of flavonoids. Various mechanisms include neurotransmitter system modulation and dopaminergic, noradrenergic, and serotonergic pathways regulation in the central nervous system. Different compounds of flavonoids have antidepressant properties in vivo or in vitro experiments or clinical trials and can be used as alternative and complementary treatments for depression. In general, it was observed that there were no severe side effects.ConclusionOur study proves the antidepressant potential of flavonoids, and considering the limited side effects, they can be used as complementary medicine for depressed patients.